Screening for Multidrug-resistant (MDR) Gram-negative Organisms and Progression to Bloodstream Infections in Hematopoietic Cell Transplant (HCT) Patients: a Single-center Pilot Study. (4th October 2017) - Seo, Susan; Gedrimaite, Zivile; McMillen, Tracy; Featherstone, Cathy; Grant-Navarro, Pamela; Krist, Nicole; Papadopoulos, Esperanza; Papanicolaou, Genovefa; Babady, N Esther; Kamboj, Mini
Abstract: Background: Fluoroquinolone (FQ) prophylaxis (ppx) is routine for patients (patients) undergoing autologous (auto) or allogeneic (allo) HCT at our center since 2006. Allo HCT patients also receive vancomycin to prevent viridans streptococcal sepsis. The potential of FQ to select for resistant gram-negative (GN) bacteria, including ESBL and carbapenem-resistant (CR), is a concern. Active screening of patients on admission and day (D) +14 to determine FQ, ESBL, and CR colonization and progression to bloodstream infection (BSI) was performed. Preliminary results are reported. Methods: Demographics, transplant characteristics, antibiotic ppx, and relevant lab and microbiologic data were collected. Two peri-rectal swabs were collected on admission and D+14 for each pt admitted for auto or allo HCT. Swabs were plated on specialized media to ascertain for FQ-R, ESBL, and CR on admission and D+14. Primary outcome was breakthrough BSI within 2 weeks of HCT. Results: Between January 1, 2017 and February 22, 2017, 55 were admitted for HCT: 26 auto and 29 allo. Average (avg) age was 53 years, 53% were men. Transplant characteristics are in Table 1. In contrast to allo, auto patients had median shorter FQ ppx (11.5 vs. 14 days) and neutropenia (5 vs. 13 days) as well as avg shorter hospital stay (21 vs. 31 days). Among 26 auto patients, admit swabs were positive for FQ-R Escherichia coli in 3 (12%), ESBL E. coli in 2 (8%), and CR in 0 (0%); D+14 swabs were positive for FQ-R E. coli in 2 (8%; one positive on admit), ESBL E. coli in 1 (4%, positive on admit), and CR Acinetobacter baumannii in 1 (4%). Among 29 allo, admit swabs were positive for FQ-R E. coli in 1 (3%) and CR E. coli in 1 (3%); none had positive D+14 swabs. Overall BSI rate was 17% for allo and 8% for auto. No GN BSI occurred among the 55 HCT patients. There were seven Gram-positive (GP) BSI, including three VRE (all allo), one coagulase-negative staphylococcus (allo), one Corynebacterium jeikeium (allo), one MRSA (auto), and one viridans streptococcus (auto). Conclusion: Prospective screening of all patients admitted for auto and allo HCT at a large tertiary care cancer center with a geographically diverse referral pattern showed low admission prevalence of FQ-R and negligible ESBL and CR carriage. No cases of acquisition were detected. All BSI episodes were due to GP organisms. Knowledge of local epidemiology in high-risk settings can help guide rational antibiotic use. Disclosures: All authors: No reported disclosures.